3D Printing with MatterControl - Horvath, Joan. (Apress : Imprint: Apress, 2015)
In 3D Printing With MatterControl, Joan Horvath and Rich Cameron, the team behind Mastering 3D Printing, explain step-by-step how to use the MatterControl program, which allows you to control many common types of 3D printers (including both cartesian and delta style machines). 3D Printing With MatterControl can stand alone, or it can be a companion to Mastering 3D Printing to show you how to install, configure, and use best practices with your printer and printing software. The book includes both step by step software walkthroughs and case studies with typical 3D printed objects. Whether you are a "maker" or a teacher of makers, 3D Printing with MatterControl will show you how to get the most out of your printer with the new standard for open source 3D printing software. While there are books available on 3D printers, and even a few on software to make models for printers, there are few good sources covering the software that actually controls these printers. MatterControl is emerging as the leading open source software for 3D printers, and  3D Printing With MatterControl covers this new standard in this brief book.